Sekolah dan Masyarakat dalam Perspektif Alquran - Hendra Kurniawan; Suaib H. Muhammad; Ali Hamdan (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
The community is all actors in the institutional context referred to as potential stakeholders. That is the group that has the decisions to be made regarding the educational agenda and the organizations that participate in the educational decision process. The school's relationship with the community aims to : 1) Advancing the quality of learning and children's growth, 2) Strengthening goals and improving the quality of life and livelihoods of the community, and 3) Encouraging the community in establishing relationships with schools. The function of the community in education is as a source that provides students, teachers, facilities and infrastructure in school administration. In addition, the community is also a consumer of the results of school education, who receives back and provides employment for school graduates, then as participants in the education process at school, who continuously follows and influences the education process in schools. Some of the surahs in the Qur'an that allude to society and educational institutions or world developments are: 1) QS. al Fath : 48:8, 2) QS. al Maidah: 5:2 dan 67, 3) QS. adz Dzariyat: 51:55.